Educating Students' Character Based on Values Through Extracurricular Activities - Salman, Salman; Amelia Lubis, Riska; Zilfaroni, Zilfaroni (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2023)
Character in the world of education is highly expected to be able to make students have a good attitude or character for themselves. This character is a characteristic of each individual to live and work together as it can encourage someone to act, speak and respond to something. Scouting activities are one of the extracurricular activities to shape student character. This study aims to find out about the implementation of Morse activities, Marching Activities, Pioneering Activities, Code Activities, Semaphore Activities in character building of students at Modern Islamic Boarding Schools in West Pasaman. This study aims to determine the pattern of value-based character education through extracurricular activities of Islamic boarding schools. This study uses a qualitative approach with a case study design to explore and understand comprehensively. The source of research data was taken from three informants consisting of the head of the mabigus, scout leader and student leader of the scout organization. The results of the study show that 1) Morse activities, marching regulations (PBB), pioneering, code and semaphore at Islamic Boarding School are taught with objectives, benefits for students to be active, the role of students with religious values ​​and characters instilled in students, the existence of strategies with frequent practice, target achievement, the existence of obstacles, solutions to each obstacle, development is seen in achievements with evidence stored in the school inventory room.